THE ROLE OF STOCK MARKET DEVELOPMENT IN SHAPING INTERNATIONAL FINANCIAL CENTRES (American Journal of Business Management, Economics and Banking, 2025)
This article examines the evolution and strategic positioning of international financial centres (IFCs), with particular emphasis on the pivotal role of stock markets in enhancing financial system efficiency. It explores how stock exchanges contribute to market liquidity, enable effective capital mobilization, and act as a catalyst for financial innovation, all of which are essential factors in the global competitiveness of financial hubs. The study presents a detailed analysis of Uzbekistan’s trajectory within the Global Financial Centres Index (GFCI), highlighting its efforts to strengthen capital market institutions and align with international financial standards.